2022
DOI: 10.1111/odi.14291
|View full text |Cite
|
Sign up to set email alerts
|

Confocal microscopy in oral cancer and oral potentially malignant disorders: A systematic review

Abstract: ObjectiveTo systematically identify and summarise current research on the utility of confocal microscopy in oral squamous cell carcinoma and oral epithelial dysplasia in oral potentially malignant disorders.MethodsDatabases Medline, Embase, Evidence‐Based Medicine, and Web of Science were searched with articles screened and included if their primary objective was the use of a confocal microscope in diagnosis of oral cancer or epithelial dysplasia, in vivo or ex vivo.Results and DiscussionTwenty‐eight relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…In this study, we demonstrate the performance of fsdCLE as a chairside technology for diagnostic assessment of oral mucosal lesions and determine its accuracy in the diagnosis of dysplasia/carcinoma compared with conventional histopathology. Several previous studies using ppCLE technology have demonstrated the possibility and limitations of applying CLE in vivo to malignancy and premalignancy in the head and neck region 10,13 but none have determined the ability of CLE to be used as a point-of-care diagnostic device offering on-thefly microscopic imaging data. Additionally, none have determined the use of acriflavine hydrochloride as contrast imaging agent for determination of cellular and subcellular features of oral tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we demonstrate the performance of fsdCLE as a chairside technology for diagnostic assessment of oral mucosal lesions and determine its accuracy in the diagnosis of dysplasia/carcinoma compared with conventional histopathology. Several previous studies using ppCLE technology have demonstrated the possibility and limitations of applying CLE in vivo to malignancy and premalignancy in the head and neck region 10,13 but none have determined the ability of CLE to be used as a point-of-care diagnostic device offering on-thefly microscopic imaging data. Additionally, none have determined the use of acriflavine hydrochloride as contrast imaging agent for determination of cellular and subcellular features of oral tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Reflectance and fluorescence ppCLE devices have been used in pilot studies of oral lesions including oral leukoplakia and OSCC (reviewed in 13 ). These have either performed imaging ex vivo using freshly excised tissue, 14 or produced inadequate images during capture requiring development and validation of a classification system for diagnosis for OSCC 15 .…”
Section: Introductionmentioning
confidence: 99%
“…So far, confocal microscopy and its non-linear counterpart multiphoton microscopy have been considered the gold standard techniques for fluorescence bioimaging ( Ramani et al, 2022 ; Teo et al, 2022 ). Confocal microscopes can eliminate out-of-focus signals by placing a pinhole aperture at the conjugate point of the focus of the detecting objective lens and the focus of the concentrator.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in the diagnosis of oral diseases, neural networks can be trained on large datasets of macrographs, micrographs, histopathology slide images, and other sources of patient data. 7 These networks can learn complex patterns and features from this data, enabling them to make accurate diagnoses with high sensitivity and specificity. 8 Upon analyzing patient data, such as medical and dental histories, genetic information, and imaging results, these deep learning models could recommend personalized treatment strategies.…”
mentioning
confidence: 99%
“…In oral medicine, deep learning and neural networks can be utilized for various tasks such as disease diagnosis, treatment planning, and outcome prediction. For instance, in the diagnosis of oral diseases, neural networks can be trained on large datasets of macrographs, micrographs, histopathology slide images, and other sources of patient data 7 . These networks can learn complex patterns and features from this data, enabling them to make accurate diagnoses with high sensitivity and specificity 8 .…”
mentioning
confidence: 99%